2009
DOI: 10.1063/1.3253753
|View full text |Cite
|
Sign up to set email alerts
|

Optically active Er3+ ions in SiO2 codoped with Si nanoclusters

Abstract: Optical properties of directly excited erbium ͑Er 3+ ͒ ions have been studied in silicon rich silicon oxide materials codoped with Er 3+ . The spectral dependence of the direct excitation cross section ͑ dir ͒ of the Er 3+ atomic 4 I 15/2 → 4 I 11/2 transition ͑around 0.98 m͒ has been measured by time resolved -photoluminescence measurements. We have determined that dir is 9.0Ϯ 1.5 ϫ 10 −21 cm 2 at 983 nm, at least twice larger than the value determined on a stoichiometric SiO 2 matrix. This result, in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
(27 reference statements)
3
23
0
Order By: Relevance
“…The value of f Exc is as high as 53% for the SE film and 23% for the ES film, which are among the largest ever reported 4 This proves the high efficiency of the excitation process in our as-deposited films. Of further note is the fact that there is a large increase in f Exc , by a factor 53%, which occurs when the order of the dopant deposition is changed.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The value of f Exc is as high as 53% for the SE film and 23% for the ES film, which are among the largest ever reported 4 This proves the high efficiency of the excitation process in our as-deposited films. Of further note is the fact that there is a large increase in f Exc , by a factor 53%, which occurs when the order of the dopant deposition is changed.…”
supporting
confidence: 49%
“…1 This limitation arises because codoping is usually performed by mixing the Si and Er components such that there is no control over their local relative position and thus their separation. [2][3][4] This limits the percentage of Er 3+ ions that are optically excited, usually to values of a few percent; and only recently has a value of 23% been achieved. 4 This is still far below the excitation fraction of 50% that is considered to be necessary to achieve gain, as has been proposed by recent reports, which suggest different routes to improve the excitation by achieving a longer excitation energy-transfer distance, 5 by using alternative excitation routes such as Si-related luminescent centers, 6,7 or by Er-doping of amorphous silicon-rich oxides.…”
mentioning
confidence: 99%
“…There is consensus in the literature that the principal reason obstructing the optical gain achievement in this material is a low fraction of sensitized erbium ions [7][8][9][10]. Recently, we have demonstrated that this is followed by the loss of light emission capability of Er 3+ when embedded in SRO material [11]. While the main fraction of embedded erbium ions does not participate in the process of light emission, absorption properties of non-emitting ions remain unaltered [12].…”
Section: Introductionmentioning
confidence: 99%
“…These samples are particularly interesting since they show the highest to date fraction of Er ions coupled to Si-np ͑ϳ52%͒, 13 which produces an internal gain in waveguide samples of about 1 dB/cm. 14 In this study, we have demonstrated that the physics behind the transfer mechanism does not depend on the Si-np nature; in particular, we have verified that Auger back transfer processes are negligible in crystalline Si-nc samples, confirming the previous results obtained in amorphous Si-np.…”
Section: Discussionmentioning
confidence: 99%